Sustainable Micro-Social Enterprises in India: A Quantitative Study of Crucial Factors Leading to Their Financial Sustainability - D'Mello, Rolvin Vincent (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Social enterprises strive to create social value by providing innovative solutions to various socio-economic and developmental problems. Given the harsh economic terrain, the key question is how these organizations traverse the path to financial sustainability to fulfil their social mission. Thus often challenged to either change scope or shut down. There is a dearth of research on micro-social enterprises and their strategies for financial sustainability. This study gathered data through an online survey platform from 121 social enterprises, which were more than 3 years of age based in the Indian state of Maharashtra. Further, crucial insights were obtained by analyzing this data using two statistical software: Jamovi and PROCESS Macro of SPSS for serial mediation. The findings demonstrate that growth orientation positively and significantly influences financial sustainability, both directly, and indirectly through; product & service innovation, social capital and external funding, which was observed individually and in serial mediation. Thus revealing that all these factors have partial mediation on financial sustainability. However, the influence of growth orientation with all these factors is way higher than it does individually. There are several crucial paths for financial sustainability, however, the most crucial one is when growth orientation is in tandem with product & service innovations. By harnessing the synergies between growth-oriented strategies and intermediary variables, social enterprises can navigate challenges, seize opportunities, and advance their dual mission of financial sustainability as well as their social mission.